RETRACTED: Formation of resilience, ecocentric worldview, conscious citizenship for the purpose of physical improvement and patriotic education of teenage athletes - Bayer Elena; Gonchar Oksana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001